Pengaruh Gross Profit Margin, Current Ratio, Dan Price Earning Ratio Terhadap Harga Saham Pada PT Indofood CBP Sukses Makmur TBK Periode 2015-2024 - Ardi Bachtiar; Rafi Azzarqi Maulidi (Journal of Innovative and Creativity, 2026)
This study aims to determine the effect of Gross Profit Margin on Stock Prices at PT Indofood CBP Sukses Makmur Tbk, to determine the effect of Current Ratio on Stock Prices at PT Indofood CBP Sukses Makmur Tbk, and to determine the effect of Price Earning Ratio on Stock Prices at PT Indofood CBP Sukses Makmur Tbk, as well as to determine the effect of Gross Profit Margin, Current Ratio, and Price Earning Ratio simultaneously on Stock Prices at PT Indofood CBP Sukses Makmur Tbk. The independent variables used in this study are Gross Profit Margin, Current Ratio, and Price Earning Ratio, while the dependent variable used in this study is Stock Price. The research method used is quantitative method using a descriptive approach. The population in this study is in the form of financial statements for 10 years, namely the 2015-2024 period. The results of the t test or partially this study indicate that Gross Profit Margin has a positive effect on Stock Price with tcount > ttable (2.885 > 2.447) and a significance level (0.028 < 0.05), Current Ratio has no significant effect on Stock Price with tcount < ttable (0.932 < 2.447) and significance level (0.387 > 0.05), and Price Earning Ratio has a positive effect on Stock Price with tcount > ttable (4.984 > 2.447) and significance level (0.002 < 0.05). The results of the F test or simultaneously this study indicate that Gross Profit Margin, Current Ratio, and Price Earning Ratio have a positive effect on Stock Price with Fcount > Ftabel (10.388 > 4.76) and a significance level of (0.009 < 0.05).